Cardiovascular side-effects of antipsychotic drugs: The role of the autonomic nervous system - Leung, Joanne Y.T.; Barr, Alasdair M.; Procyshyn, Ric M.; Honer, William G.; Pang, Catherine C.Y. (Pharmacology & therapeutics (Oxford), 2012)
Cardiovascular disease is the leading cause of death in people with severe mental disorders, and rates are proportionally greater than for other diseases such as cancer. Reports of sudden death in patients receiving antipsychotic treatment have raised concerns about the safety of antipsychotic drugs, leading to a number of recent changes in how such drugs are advertised and marketed. The majority of second generation antipsychotic drugs also have significant metabolic side-effects, such as weight gain, insulin resistance and hyperlipidemia, which may contribute indirectly to cardiovascular complications. As the use of antipsychotic drugs continues to expand into new indications and populations such as children and adolescents, a better understanding is needed of how antipsychotic drugs affect the cardiovascular system. Antipsychotic drugs interact with numerous receptors both centrally and peripherally, including monoamine receptors. The direct, non-specific pharmacological actions of antipsychotic drugs can lead to adverse cardiovascular effects, including orthostatic hypotension, tachycardia and ventricular arrhythmias. The mechanisms responsible for these antipsychotic-induced cardiovascular abnormalities have not been fully elucidated, but likely involve blockade of adrenergic or cholinergic receptors and hERG channels, in addition to impaired autonomic function. The direct and indirect effects of antipsychotic drugs on the cardiovascular system and their possible mechanisms of action are discussed in this review, where both preclinical and clinical findings are integrated.